2018
DOI: 10.3390/ijerph15081736
|View full text |Cite
|
Sign up to set email alerts
|

Grief and Avoidant Death Attitudes Combine to Predict the Fading Affect Bias

Abstract: The fading affect bias (FAB) occurs when unpleasant affect fades faster than pleasant affect. To detect mechanisms that influence the FAB in the context of death, we measured neuroticism, depression, anxiety, negative religious coping, death attitudes, and complicated grief as potential predictors of FAB for unpleasant/death and pleasant events at 2 points in time. The FAB was robust across older and newer events, which supported the mobilization-minimization hypothesis. Unexpectedly, complicated grief positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…The data for the alcohol study came from the four events provided by the 261 participants in the second study published by Gibbons et al (2013). The data for the death study came from the four events provided by each of the 236 participants in the study published by Gibbons et al (2016), and the data for the human and pet death study came from the four events provided by the 198 participants in the Gibbons, Fehr, et al (2018) study. Finally, the data for the presidential election study came from the four events provided by the 311 participants in the Gibbons, Thomas, and Dunlap (2018) study.…”
Section: Participantsmentioning
confidence: 99%
“…The data for the alcohol study came from the four events provided by the 261 participants in the second study published by Gibbons et al (2013). The data for the death study came from the four events provided by each of the 236 participants in the study published by Gibbons et al (2016), and the data for the human and pet death study came from the four events provided by the 198 participants in the Gibbons, Fehr, et al (2018) study. Finally, the data for the presidential election study came from the four events provided by the 311 participants in the Gibbons, Thomas, and Dunlap (2018) study.…”
Section: Participantsmentioning
confidence: 99%
“…Gibbons et al (2016) studied FAB in regard to the memories of the loss of loved ones described by a primarily white, primarily female sample of American undergraduates ( M = 19.7 years old) and found that FAB was robust for everyday and significant events, but FAB decreased if people used negative religious coping (a more negative insecure relationship with God) for death events. Building upon that research, Gibbons et al (2018) sampled mainly white, mainly female American undergraduates ( M = 19.6 years of age) and gathered descriptions of pet or human losses and comparable pleasant events earlier in time and later in time in their FAB procedure. Findings indicated that there was a robust FAB for pet and human death events, and that older death events evidenced more FAB than newer death events.…”
Section: Fab In Memories For the Loss Of Loved Onesmentioning
confidence: 99%
“…The FAB occurs within 24 hr, it persists for 3 months (Gibbons, Lee, & Walker, 2011), it increases after 3 months (Walker et al, 1997), and it is related to individual difference variables (Skowronski, Walker, Henderson, & Bond, 2014). The FAB is a generalizable phenomenon that persists across cultures (Ritchie, Walker, Marsh, Hart, & Skowronski, 2014) and event types including alcohol (Gibbons et al, 2013), religion (Gibbons, Hartzler, Hartzler, Lee, & Walker, 2015), death (Gibbons et al, 2016; Gibbons, Lee, Fehr, Wilson, & Marshall, 2018), social media (Gibbons et al, 2017), and videogames (Gibbons & Bouldin, 2019). The researchers studying the FAB argue that it makes life pleasant by reducing the effects of unpleasant events, maintaining the effects of pleasant events, and helping people seek pleasant experiences (Ritchie, Walker, et al,; Walker & Skowronski, 2009; Walker, Skowronski, & Thompson, 2003).…”
Section: Fading Affect Biasmentioning
confidence: 99%